Italia 1943-1945 : le ragioni della violenza - Angelo Ventrone (Amnis)
After the arrest of Mussolini July 25, 1943, in front of what Italians think as the fall of fascism and the end of the war, they find their political references in national symbols. But two events changed everything: the armistice of 8 September 1943 and the flight of the King and the government from Rome. In those moments, even in response to the German occupation of the country, the Resistance movement begins to take shape around the anti-fascist parties. Thus a war of national liberation starts. However, after the birth of the Social Republic of Mussolini and until the Liberation in April 1945, the latter joins both a civil war and a social war, fought by the Communist groups. However, in addition to armed resistance, also arises a « civil resistance », less visible, but equally important, to explain how Italians have moved away from fascism.